Negative electrode sheet, method for manufacturing the same, and solid-state battery

CN122889690APending Publication Date: 2026-10-09CHENGDU YIWEI LITHIUM ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610960620.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本申请提供一种负极片及其制备方法、固态电池,旨在解决现有的涂碳层在电池的循环过程中存在锂沉积不均匀、涂碳层结构不稳定问题

Benefits of technology

[0008]本申请通过调控微纳米碳基骨架材料、亲锂性微纳米金属材料和微纳米金属基骨架材料的粒径比例,使复合碳层中的微纳米碳基骨架材料、亲锂性微纳米金属材料和微纳米金属基骨架材料协同效果更好,促进锂离子的均匀沉积,并维持复合碳层的结构稳定性,提高电池的性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889690A_ABST
    Figure CN122889690A_ABST
Patent Text Reader

Abstract

The application discloses a negative electrode sheet and a preparation method thereof and a solid-state battery, and belongs to the technical field of batteries. The negative electrode sheet comprises a negative electrode current collector and a composite carbon layer. The composite carbon layer is arranged on at least one side of the negative electrode current collector. The composite carbon layer comprises a micro-nano carbon-based skeleton material, a lithiumophilic micro-nano metal material and a micro-nano metal-based carbon skeleton reinforcing material. The D50 particle size of the micro-nano carbon-based skeleton material is D1, the D50 particle size of the lithiumophilic micro-nano metal material is D2, and the D50 particle size of the micro-nano metal-based carbon skeleton reinforcing material is D3. 0.6 <= D1 / D2 <= 15, 0.3 <= D1 / D3 <= 10, and 0.6 <= D3 / D2 <= 5. The lithiumophilic sites are uniformly distributed in the composite carbon layer through the cooperation of the characteristics and particle sizes of the micro-nano carbon-based skeleton material, the lithiumophilic micro-nano metal material and the micro-nano metal-based carbon skeleton reinforcing material, so that the lithium ions are uniformly deposited, and the stability of the composite carbon layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a negative electrode sheet and its preparation method, and a solid-state battery. Background Technology

[0002] Sulfide-based all-solid-state batteries are considered the most promising next-generation battery system due to their inherent high safety, high energy density (volume / gravimetric energy density), and excellent interface compatibility. Among them, lithium metal anodes are considered one of the best candidate anodes for developing high-energy-density all-solid-state batteries due to their ultra-high theoretical specific capacity (3860 mAh / g). However, lithium metal anodes are prone to lithium dendrite formation, and significant volume expansion and contraction occur during deposition and stripping, severely affecting the battery's cycle life and potentially causing serious safety accidents. Furthermore, lithium metal is relatively soft and not resistant to high voltage, making the high-voltage manufacturing of lithium metal-based all-solid-state batteries extremely difficult, further limiting their application.

[0003] In related technologies, in order to improve the cycle life of batteries, researchers have proposed carbon-coated anode batteries. Carbon-coated anode batteries do not contain negative electrode active materials, but instead coat the current collector with a carbon layer. However, existing carbon coatings have drawbacks such as uneven lithium deposition and unstable carbon coating structure during battery cycling. Summary of the Invention

[0004] This application provides a negative electrode sheet and its preparation method, as well as a solid-state battery, aiming to solve the problems of uneven lithium deposition and unstable carbon coating structure in existing carbon coating layers during battery cycling.

[0005] In a first aspect, this application provides a negative electrode sheet, comprising: Negative current collector; and A composite carbon layer is disposed on at least one side of the negative electrode current collector. The composite carbon layer includes a micro / nano carbon-based framework material, a lithiophilic micro / nano metal material, and a micro / nano metal-based framework material. The D50 particle size of the micro / nano carbon-based framework material is D1, the D50 particle size of the lithiophilic micro / nano metal material is D2, and the D50 particle size of the micro / nano metal-based framework material is D3; wherein, 0.6≤D1 / D2≤15, 0.3≤D1 / D3≤10, and 0.6≤D3 / D2≤5.

[0006] In this application, the particle size ratios of the micro / nano carbon-based framework material, the lithiophilic micro / nano metal material, and the micro / nano metal-based framework material in the composite carbon layer satisfy a specific relationship. The micro / nano carbon-based framework material constitutes the framework of the composite carbon layer and forms a three-dimensional conductive network within it. The lithiophilic micro / nano metal material effectively reduces the lithium nucleation energy and induces rapid lithium ion deposition. The micro / nano metal-based framework material exhibits high strength and ductility, thereby enhancing the strength of the carbon framework. By combining highly conductive micro / nano carbon-based framework material, lithiophilic micro / nano metal material, and high-strength, high-ductility micro / nano metal-based framework material, and utilizing the properties of these three materials and their synergistic particle size distribution, the three materials achieve a specific... The stacking method involves the formation of a rich porous structure from micro- and nano-carbon-based framework materials. Lithophilic micro- and nano-metallic materials are uniformly dispersed within these pores, creating uniformly distributed lithiophilic sites and a conductive network within the composite carbon layer. Simultaneously, the micro- and nano-metallic framework materials can overlap and cooperate with the micro- and nano-carbon-based framework materials, improving the stacking stability between different particles and ensuring good framework stability of the composite carbon layer. This allows lithium ions to be uniformly and rapidly deposited in the composite carbon layer during battery cycling, while also constraining volume changes in the composite carbon layer, resulting in good stability and sustained, orderly lithium ion deposition. This prevents the growth of lithium dendrites and improves the electrochemical performance of the negative electrode.

[0007] In one embodiment, 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, and 1≤D3 / D2≤3.3.

[0008] This application improves the synergistic effect of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in the composite carbon layer by adjusting the particle size ratio of these materials. This promotes uniform lithium-ion deposition, maintains the structural stability of the composite carbon layer, and enhances battery performance.

[0009] In one embodiment, 30nm ≤ D1 ≤ 300nm; and / or, 20nm ≤ D2 ≤ 50nm; and / or, 30nm ≤ D3 ≤ 100nm.

[0010] The stacking of micro / nano carbon-based framework materials with suitable particle size in this application forms a porous structure with suitable pore size and porosity, providing sufficient and uniform deposition sites for lithium ions and forming a continuous conductive network to promote efficient electron transport and reduce interfacial impedance. The suitable particle size of the lithiophilic micro / nano metal materials results in a large specific surface area, forming more and denser nucleation sites in the composite carbon layer, and making it easier to uniformly embed into the gaps of the micro / nano carbon-based framework materials, thus ensuring sufficient lithiophilic micro / nano metal materials in the composite carbon layer. The D50 particle size of the suitable micro / nano metal-based framework materials can fully overlap with the micro / nano carbon-based framework materials, forming mechanical support and structural reinforcement, better improving the strength of the carbon framework, and mitigating the volume expansion and stress impact caused by lithium deposition and stripping during charging and discharging.

[0011] In one embodiment, in the composite carbon layer, the mass of the micro / nano carbon-based framework material accounts for 60% to 95% of the mass of the composite carbon layer, the mass of the lithiophilic micro / nano metal material accounts for 1% to 20% of the mass of the composite carbon layer, and the mass of the micro / nano metal-based framework material accounts for 1% to 20% of the mass of the composite carbon layer.

[0012] The appropriate proportion of micro / nano carbon-based framework material in this application can better form the framework structure of the composite carbon layer, improve the mechanical strength of the composite carbon layer, and form a porous structure with uniform pore size and continuous channels; the appropriate proportion of lithiophilic micro / nano metal material can provide an appropriate number of lithiophilic sites for the composite carbon layer, promoting the rapid deposition of lithium ions in the composite carbon layer; the appropriate proportion of micro / nano metal-based framework material can be more uniformly dispersed in the composite carbon layer and better overlap with the micro / nano carbon-based framework material, providing sufficient support, while not destroying the conductive network structure, significantly improving the mechanical strength, anti-expansion ability and structural stability of the composite carbon layer.

[0013] In one embodiment, the composite carbon layer comprises 65% to 85% of the mass of the micro / nano carbon-based framework material, 5% to 15% of the mass of the lithium-loving micro / nano metal material, and 5% to 15% of the mass of the micro / nano metal-based framework material.

[0014] This application improves the battery performance by adjusting the mass ratio of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in a composite carbon layer. This allows the three materials to form a mutually complementary and encapsulating structure, enhancing their synergistic effect, promoting uniform lithium-ion deposition, maintaining the structural stability of the composite carbon layer, and improving battery performance.

[0015] In one embodiment, the micro / nano carbon-based framework material includes at least one of carbon black and hard carbon; and / or, the lithiophilic micro / nano metal material includes at least one of zinc nanoparticles, tin nanoparticles, bismuth nanoparticles, magnesium nanoparticles, and aluminum nanoparticles; and / or, the micro / nano metal-based framework material includes at least one of nickel nanoparticles, copper nanoparticles, and indium nanoparticles; and / or, the negative electrode current collector includes at least one of stainless steel foil, nickel foil, and copper foil.

[0016] This application uses spherical carbon black, which is more likely to form a connected and uniform porous structure, reducing the resistance to lithium-ion transport and promoting the uniform and rapid deposition of lithium-ions. Hard carbon has a rich porous structure and relatively good ionic conductivity, which can promote the transport and deposition of lithium-ions. The selected lithium-loving micro- and nano-metallic materials all have excellent affinity with lithium, which can effectively reduce the overpotential for lithium nucleation, induce uniform lithium deposition, and improve the cycle life, capacity, and safety performance of the battery. The selected micro- and nano-metallic matrix framework materials have high hardness and plasticity, and strong interfacial bonding with micro- and nano-carbon matrix framework materials, thereby improving the structural stability of the composite carbon layer and the negative electrode sheet. The selection of negative electrode current collectors made of different materials can be applied to different scenarios.

[0017] In one embodiment, the thickness of the composite carbon layer is 1 μm to 10 μm.

[0018] The appropriate thickness of this application results in a short ion transport distance for lithium ions during the deposition process, ensuring that lithium ions can quickly and smoothly reach the nucleation sites, achieving uniform, dense, and planar deposition of lithium ions, and improving the battery capacity.

[0019] In one embodiment, the composite carbon layer further includes a binder, the mass of which accounts for 2% to 10% of the mass of the composite carbon layer.

[0020] The appropriate proportion of binder in this application can more tightly bond the micro / nano carbon-based framework material, the lithium-loving micro / nano metal material, and the micro / nano metal-based framework material, thereby improving the mechanical strength of the composite carbon layer. It can also make the composite carbon layer bond more tightly with the negative electrode current collector, thereby improving the peeling force of the negative electrode sheet.

[0021] Secondly, this application provides a method for preparing the negative electrode sheet provided in the first aspect of this application, comprising: Provide negative electrode current collector; A carbon coating slurry is obtained by mixing micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, micro / nano metal-based framework materials, binders, and solvents. The solid content of the carbon coating slurry is 20wt%~30wt%. A carbon coating slurry is applied to at least one side of the negative electrode current collector, and after drying, a composite carbon layer is formed on the surface of the negative electrode current collector.

[0022] This application first obtains a carbon coating slurry and controls the solid content of the carbon coating slurry to be 20wt%~30wt%, so that the carbon coating slurry can be uniformly coated on the negative electrode current collector and form the required pore structure, providing favorable conditions for lithium ion transport and deposition; then the carbon coating slurry is coated on at least one side of the current collector and dried. The whole preparation process is simple and the production cycle is short.

[0023] Thirdly, this application provides a solid-state battery, including the negative electrode sheet provided in the first aspect of this application or the negative electrode sheet prepared by the method for preparing the negative electrode sheet provided in the second aspect of this application.

[0024] The solid-state battery of this application can achieve uniform deposition of lithium ions during charging, reduce the growth of lithium dendrites, maintain the structural stability of the negative electrode and the solid-state battery, and improve the capacity, safety and cycle life of the solid-state battery. Attached Figure Description

[0025] Figure 1 This is the first charge-discharge curve of the solid-state battery in Embodiment 5 of this application at 0.2C. Detailed Implementation

[0026] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0027] This application provides a negative electrode sheet and its preparation method, as well as a solid-state battery. Detailed descriptions are provided below. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative and do not impose numerical requirements or establish an order. Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the corresponding range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.

[0028] The technical solution of this application is as follows: In a first aspect, embodiments of this application provide a negative electrode sheet, which includes a negative electrode current collector and a composite carbon layer. The composite carbon layer is disposed on at least one side of the negative electrode current collector. The composite carbon layer includes a micro / nano carbon-based framework material, a lithiophilic micro / nano metal material, and a micro / nano metal-based framework material. The D50 particle size of the micro / nano carbon-based framework material is D1, the D50 particle size of the lithiophilic micro / nano metal material is D2, and the D50 particle size of the micro / nano metal-based framework material is D3; wherein, 0.6≤D1 / D2≤15, 0.3≤D1 / D3≤10, and 0.6≤D3 / D2≤5.

[0029] In this application, by providing a composite carbon layer on at least one side of the negative electrode current collector, when the negative electrode sheet is applied to a battery, during battery charging, lithium ions are extracted from the positive electrode sheet and deposited in the composite carbon layer on the surface of the negative electrode current collector. The composite carbon layer of this application includes micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials, and the particle size ratios of the micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials satisfy a specific relationship. First, the micro / nano carbon-based framework materials constitute the framework of the composite carbon layer and construct a continuous conductive path, forming a three-dimensional conductive network in the composite carbon layer to ensure efficient electron transport. At the same time, micro / nano carbon-based framework materials with suitable particle sizes are stacked to form a rich porous structure, ensuring efficient lithium ion transport and providing sites and volume expansion buffer space for lithium ion deposition. Second, the lithiophilic micro / nano metal materials can act as lithium... Nucleation sites effectively reduce the nucleation energy of lithium, inducing rapid lithium-ion deposition. Simultaneously, appropriately sized lithiophilic micro / nano metal materials allow for uniform dispersion within the pores formed by the micro / nano carbon-based framework, guiding lithium-ion deposition uniformly into the composite carbon layer, inhibiting dendrite growth, and improving the structural stability and electrochemical performance of the negative electrode. Furthermore, the high strength and plasticity of the micro / nano metal-based framework enhance the strength of the carbon framework. The appropriately sized framework can overlap and coordinate with the carbon-based framework, improving the stacking stability between different particles. This also ensures the stable dispersion of the lithiophilic micro / nano metal materials within the carbon framework, guaranteeing the strength of the carbon framework, improving the mechanical strength and structural stability of the composite carbon layer, without disrupting the conductive and lithiophilic network. This constrains volume changes in the composite carbon layer, buffers stress, and allows for continuous and stable lithium-ion deposition within the composite carbon layer.

[0030] Specifically, this application combines highly conductive micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and high-strength, highly ductile micro / nano metal-based framework materials. Utilizing the properties and particle size synergy of these three materials, they are stacked in a specific manner to form uniformly distributed lithiophilic sites and a conductive network within the composite carbon layer. This ensures good framework stability of the composite carbon layer, allowing for uniform and rapid deposition of lithium ions during battery cycling. It also constrains volume changes within the composite carbon layer, resulting in high stability, sustained and orderly lithium ion deposition, and prevention of lithium dendrite growth, thus improving the electrochemical performance of the negative electrode. Furthermore, its application in a sulfide all-solid-state battery system demonstrates excellent electrochemical performance.

[0031] In some embodiments, 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, and 1≤D3 / D2≤3.3.

[0032] In this application, by adjusting the particle size ratio of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials, such that 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, and 1≤D3 / D2≤3.3, the synergistic effect of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in the composite carbon layer can be improved, promoting uniform deposition of lithium ions, maintaining the structural stability of the composite carbon layer, and improving battery performance.

[0033] In some embodiments, 30nm≤D1≤300nm, for example, D1 can be 30nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, etc.

[0034] In this application, by making the D50 particle size of the micro / nano carbon-based framework material 30nm~300nm, the micro / nano carbon-based framework material with a suitable particle size allows different carbon materials to overlap and stack to form a pore structure with suitable pore size and porosity, providing sufficient and uniform deposition sites for lithium ions. At the same time, the stacked micro / nano carbon-based framework material forms a continuous conductive network, which promotes the effective transport of electrons, reduces interfacial impedance, ensures a rapid and uniform supply of electrons, and further promotes the transport and deposition of lithium ions.

[0035] In some embodiments, 20nm≤D2≤50nm, for example, D2 can be 20nm, 30nm, 40nm, 50nm, etc.

[0036] It is understandable that the suitable particle size of the lithiophilic micro / nano metal materials results in a larger specific surface area, leading to more and denser nucleation sites in the composite carbon layer, which in turn promotes the deposition of lithium ions in the composite carbon layer. Furthermore, the lithiophilic metal materials with suitable particle size are more likely to be uniformly embedded in the gaps between the micro / nano carbon-based framework materials, resulting in sufficient lithiophilic micro / nano metal materials in the composite carbon layer, which further promotes the uniform deposition of lithium ions in the composite carbon layer.

[0037] In some embodiments, 30nm≤D3≤100nm, for example, D3 can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc.

[0038] Understandably, by making the D50 particle size of the micro / nano metal matrix framework material 30nm~100nm, the D50 particle size deviation between the micro / nano metal matrix framework material and the micro / nano carbon matrix framework material is small. This allows the reinforcing micro / nano materials to better fill the pore structure of the micro / nano carbon matrix framework material, or to better overlap with the micro / nano carbon matrix framework material, forming mechanical support and structural reinforcement. This better improves the strength of the carbon framework, alleviates the volume expansion and stress impact caused by lithium deposition and stripping during charging and discharging, and avoids carbon layer cracking, pulverization, and detachment.

[0039] In some embodiments, the mass of the micro / nano carbon-based framework material in the composite carbon layer accounts for 60% to 95% of the mass of the composite carbon layer, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc.; the mass of the lithiophilic micro / nano metal material accounts for 1% to 20% of the mass of the composite carbon layer, for example, 1%, 5%, 10%, 15%, 20%, etc.; and the mass of the micro / nano metal-based framework material accounts for 1% to 20% of the mass of the composite carbon layer, for example, 1%, 5%, 10%, 15%, 20%, etc.

[0040] In this application, by making the proportion of micro / nano carbon-based framework material 60% to 95%, the appropriate proportion of micro / nano carbon-based framework material can better form the framework structure of the composite carbon layer, improve the mechanical strength of the composite carbon layer, and form a porous structure with uniform pore size and continuous channels, which is conducive to the rapid diffusion and deposition of lithium ions, and improves the reversible capacity and rate performance of the battery. The appropriate proportion of micro / nano carbon-based framework material can also enable the composite carbon layer to form a continuous and stable conductive network, ensure the rapid and uniform transmission of electrons in the composite carbon layer, make the current density distribution uniform, avoid the occurrence of lithium dendrites due to local large current, and further promote the deposition of lithium ions.

[0041] Understandably, an appropriate proportion of lithiophilic micro / nano metallic materials can provide a suitable number of lithiophilic sites for the composite carbon layer, promoting the rapid deposition of lithium ions in the composite carbon layer. At the same time, the relatively small proportion of lithiophilic micro / nano metallic materials allows them to be more evenly distributed in the composite carbon layer, thereby guiding the uniform deposition of lithium ions, forming a dense lithium deposition layer, improving battery capacity, and reducing the risk of lithium dendrite growth.

[0042] Understandably, a suitable proportion of micro / nano metal-based framework materials can be more uniformly dispersed in the composite carbon layer and better bonded with the micro / nano carbon-based framework materials, providing sufficient support without damaging the conductive network structure. This significantly improves the mechanical strength, expansion resistance, and structural stability of the composite carbon layer. Furthermore, it allows the composite carbon layer to exhibit a moderate balance between flexibility and brittleness, further enhancing its structural stability.

[0043] In some embodiments, the mass of the micro / nano carbon-based framework material in the composite carbon layer accounts for 65% to 85% of the mass of the composite carbon layer, for example, 65%, 70%, 75%, 80%, 85%, etc.; the mass of the lithiophilic micro / nano metal material accounts for 5% to 15% of the mass of the composite carbon layer, for example, 5%, 10%, 15%, etc.; and the mass of the micro / nano metal-based framework material accounts for 5% to 15% of the mass of the composite carbon layer, for example, 5%, 10%, 15%, etc.

[0044] In this application, by adjusting the mass ratio of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in the composite carbon layer, such that the mass ratios of micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in the composite carbon layer are 65%~85%, 5%~15%, and 5%~15%, respectively, the micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, and micro / nano metal-based framework materials in the composite carbon layer can form a mutually complementary and mutually encapsulating structure, thereby improving the synergistic effect of the three, promoting the uniform deposition of lithium ions, maintaining the structural stability of the composite carbon layer, and improving the performance of the battery.

[0045] In some embodiments, the micro / nano carbon-based framework material includes at least one of carbon black and hard carbon.

[0046] In this application, spherical carbon black is selected. Carbon black has good dispersibility and high structural regularity, making it easier for different particles to form a connected and uniform porous structure, reducing the resistance to lithium ion transport and promoting uniform and rapid lithium ion deposition. Hard carbon has abundant porous structure, providing sufficient channels for lithium ion transport and deposition. At the same time, its relatively good ionic conductivity can promote rapid lithium ion transport, ultimately resulting in uniform lithium ion deposition.

[0047] In some embodiments, the lithiophilic micro / nano metallic materials include at least one of zinc nanoparticles, tin nanoparticles, bismuth nanoparticles, magnesium nanoparticles, and aluminum nanoparticles.

[0048] Understandably, by appropriately selecting the types of lithium-affinity micro / nano metal materials, the aforementioned nano-metal particles all exhibit excellent affinity for lithium, effectively reducing the lithium nucleation overpotential, inducing a mild and reversible alloying reaction, promoting uniform lithium deposition, inhibiting dendrite growth, and improving the battery's cycle life, capacity, and safety performance. Furthermore, the aforementioned nano-metal particles are inexpensive, reducing costs and giving the negative electrode sheet of this application extremely high practical value and market competitiveness.

[0049] In some embodiments, the micro / nano metal matrix framework material includes at least one of nickel nanoparticles, copper nanoparticles, and indium nanoparticles.

[0050] It is understandable that by reasonably setting the types of micro-nano metal matrix framework materials, the aforementioned micro-nano metal matrix framework materials have high hardness and high plasticity, and at the same time have strong interfacial bonding force with micro-nano carbon matrix framework materials. This can not only increase the bonding tightness of different particles, but also provide deformation buffer for the carbon framework, thereby improving the structural stability of the composite carbon layer and the negative electrode sheet.

[0051] In some embodiments, the negative current collector comprises at least one of stainless steel foil, nickel foil, and copper foil.

[0052] Understandably, by selecting different types of negative electrode current collectors, stainless steel foil and nickel foil, with their high mechanical strength and rigidity, can work synergistically with the composite carbon layer to improve the structural stability of the negative electrode sheet. Copper foil, with its good conductivity, can work synergistically with the composite carbon layer to improve the conductivity of the negative electrode sheet. Choosing different negative electrode current collectors can make them suitable for different scenarios.

[0053] In some embodiments, the thickness of the composite carbon layer is 1μm to 10μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.

[0054] In this application, by reasonably setting the thickness of the composite carbon layer, the appropriate thickness results in a short ion transport distance for lithium ions during the deposition process, ensuring that lithium ions reach the nucleation sites quickly and smoothly, achieving uniform, dense, and planar deposition of lithium ions, and improving the battery capacity; the relatively thin composite carbon layer can also reduce its space occupation in the battery, further improving the energy density of the battery.

[0055] For example, the thickness of the composite carbon layer is 5μm to 8μm, such as 5μm, 6μm, 7μm, 8μm, etc.

[0056] In some embodiments, the composite carbon layer further includes a binder, the mass of which accounts for 2% to 10% of the mass of the composite carbon layer, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0057] In this application, by incorporating a binder into the composite carbon layer, the binder can more tightly bond the micro / nano carbon-based framework material, the lithium-affinity micro / nano metal material, and the micro / nano metal-based framework material, thereby improving the mechanical strength of the composite carbon layer. Simultaneously, it allows for a tighter bond between the composite carbon layer and the negative electrode current collector, increasing the peel force of the negative electrode sheet to greater than or equal to 0.4N, meeting the requirements for solid-state batteries. By rationally controlling the proportion of the binder, the structural stability of the negative electrode sheet is improved while its impact on the battery's energy density is reduced.

[0058] For example, the mass of the binder accounts for 4% to 7% of the mass of the composite carbon layer, such as 4%, 5%, 6%, 7%, etc.

[0059] For example, the adhesive includes at least one of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).

[0060] Secondly, embodiments of this application provide a method for preparing the negative electrode sheet provided in the first aspect of this application, comprising: Provide negative electrode current collector; A carbon coating slurry is obtained by mixing micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, micro / nano metal-based framework materials, binders, and solvents. The solid content of the carbon coating slurry is 20wt%~30wt%, for example, it can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, etc. A carbon coating slurry is applied to at least one side of the current collector, and after drying, a composite carbon layer is formed on the surface of the negative electrode current collector.

[0061] In this application, micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, micro / nano metal-based framework materials, binders, and solvents are first mixed to obtain a carbon coating slurry. The solid content of the carbon coating slurry is controlled to be 20wt%~30wt%, which not only ensures that the carbon coating slurry can be successfully coated on the negative electrode current collector, but also ensures that the composite carbon layer formed on the negative electrode current collector has excellent pore structure, providing favorable conditions for lithium ion transport and deposition. Then, the carbon coating slurry is coated on at least one side of the current collector. After drying, a composite carbon layer is formed on the surface of the current collector. The entire preparation process is simple, has a short production cycle, and has no complicated and cumbersome procedures, ensuring production efficiency and batch stability of products.

[0062] For example, a method for preparing a negative electrode includes: Weigh out a certain amount of micro / nano carbon-based framework material, lithium-based micro / nano metal material, and micro / nano metal-based framework material according to the proportion, and mix them thoroughly and evenly using a dry mixer to obtain carbon-based composite powder; the mixing time is 5 min to 20 min, for example, 5 min, 10 min, 15 min, 20 min, etc.

[0063] Next, the carbon-based composite powder is placed in a homogenizing tank, and the adhesive solution is added according to the ratio. The mixture is then homogenized using a homogenizer. Subsequently, the solid content of the slurry is adjusted to 20wt%~30wt%, and the viscosity is 5000mPa·s~7000mPa·s to obtain a carbon coating slurry. The adhesive solution consists of a binder and a solvent. The solvent includes at least one of N-methylpyrrolidone (NMP), p-xylene, butyl butyrate, n-heptane, anisole, and phenethyl ether.

[0064] Next, a carbon coating slurry is coated onto at least one side of the negative electrode current collector using a coating machine, and the solvent is removed by drying to obtain the negative electrode sheet.

[0065] For example, the mixing time in the process of preparing carbon-based composite powder is 10 min to 15 min.

[0066] Thirdly, embodiments of this application provide a solid-state battery, including the negative electrode sheet provided in the first aspect of this application or a negative electrode sheet prepared by the method for preparing the negative electrode sheet provided in the second aspect of this application.

[0067] In this application, the negative electrode sheet provided by the first aspect of this application or the negative electrode sheet prepared by the method provided by the second aspect of this application is applied to a solid-state battery, so that the solid-state battery can achieve uniform deposition of lithium ions during charging, reduce the growth of lithium dendrites (the composite carbon layer can also prevent the small amount of generated lithium dendrites from penetrating into the electrolyte layer, which greatly improves the electrochemical stability of the battery) and maintain the structural stability of the negative electrode sheet and the solid-state battery, thereby improving the capacity, safety and cycle life of the solid-state battery.

[0068] For example, the solid-state battery further includes a positive electrode sheet, which includes a positive electrode active layer, comprising a positive electrode active material, a sulfide solid electrolyte, and a conductive agent; wherein the positive electrode active material comprises at least one of lithium nickel cobalt manganese oxide, lithium lithium-rich manganese oxide, and lithium cobalt oxide; the sulfide solid electrolyte comprises lithium pentachloromonothiophosphate (LPSC), lithium tetrachlorodithiophosphate (LPSCl2), and bromine-chlorine-doped lithium thiophosphate (LPSC, LPSBr). x Cl 1-x At least one of the following: the conductive agent includes at least one of carbon fiber, carbon black, graphene, and carbon nanotubes.

[0069] Understandably, this application selects lithium nickel cobalt manganese oxide, lithium lithium manganese oxide, and lithium cobalt oxide, which possess high specific capacity, excellent electrochemical activity, and good lithium intercalation / deintercalation capabilities, as the core components of the positive electrode active layer. This improves the energy density and cycle life of solid-state batteries. By selecting diverse positive electrode active materials, it can adapt to different application scenarios. The aforementioned sulfide solid electrolytes have high ionic conductivity and good interfacial compatibility, effectively replacing traditional liquid electrolytes. Simultaneously, these sulfide solid electrolytes can form good contact with the positive electrode active material and conductive agent, filling the space between them to create a continuous lithium-ion transport channel penetrating the positive electrode active layer. This ensures rapid and stable lithium-ion transport within the positive electrode active layer, improving the battery's rate performance and cycle stability. The aforementioned conductive agents have good conductivity, enabling the construction of a continuous and efficient electron transport network between positive electrode active material particles, reducing the interfacial impedance of the positive electrode active layer, and lowering the internal resistance of the solid-state battery.

[0070] For example, a method for preparing a solid-state battery includes: A sulfide solid electrolyte was added to the model battery and held at 300 MPa to 500 MPa for at least 5 minutes to obtain a solid electrolyte membrane. A positive electrode active material, a sulfide solid electrolyte, and a conductive agent are mixed to obtain a positive electrode composite powder. Add the positive electrode composite powder to one side of the model battery according to a certain areal load (i.e., place the positive electrode composite powder on the side of the solid electrolyte membrane), and hold it at 300MPa~500MPa for more than 5 minutes to form a positive electrode sheet on the solid electrolyte membrane. Add the negative electrode sheet to the other side of the model battery (i.e., place the positive electrode composite powder on the other side of the solid electrolyte membrane), and hold it at a pressure of 300MPa~500MPa for more than 5 minutes to form a negative electrode sheet on the side of the solid electrolyte membrane away from the positive electrode sheet.

[0071] It is understood that the solid-state battery obtained in this application is actually a negative electrode-free battery. During the use of a negative electrode-free battery, the safety performance of the battery is improved by applying appropriate external pressure. Therefore, when performing performance tests on the solid-state battery, an external pressure of 2MPa to 5MPa needs to be applied.

[0072] The present application will be specifically described below through specific embodiments. These embodiments are only some embodiments of the present application and are not intended to limit the present application. Unless otherwise specified, the raw materials used in the following embodiments are all commercially available products.

[0073] Example 1 This embodiment provides a negative electrode sheet, which includes a stainless steel foil and a composite carbon layer. The composite carbon layer is disposed on both sides of the negative electrode current collector, and the composite carbon layer includes carbon black, nano zinc particles, nano nickel particles and PVDF.

[0074] The composite carbon layer has a thickness of 7 μm, and the stainless steel foil has a thickness of 10 μm.

[0075] The carbon black has a D50 particle size (D1) of 300 nm and accounts for 75% of the mass of the composite carbon layer; the zinc nanoparticles have a D50 particle size (D2) of 20 nm and account for 10% of the mass of the composite carbon layer; the nickel nanoparticles have a D50 particle size (D3) of 30 nm and account for 10% of the mass of the composite carbon layer; and PVDF accounts for 5% of the mass of the composite carbon layer.

[0076] Methods for preparing negative electrode sheets include: (1) Weigh carbon black, nano zinc particles and nano nickel particles, and mix them thoroughly and evenly using a dry mixer to obtain carbon-based composite powder; the mixing time is 12 min.

[0077] (2) Next, the carbon-based composite powder is placed in a homogenizing tank, the adhesive is added, and homogenized by a homogenizer. Then the solid content of the slurry is adjusted to 25wt% and the viscosity is 6000mPa·s to obtain a carbon coating slurry, wherein the adhesive is composed of PVDF and NMP.

[0078] (3) Next, carbon coating slurry is coated on both sides of stainless steel foil by a coating machine, and the solvent is removed by drying to obtain the negative electrode sheet.

[0079] Example 2 This embodiment provides a negative electrode sheet. Compared with Embodiment 1, the only difference is that the D50 particle size D1 of the carbon black is 30nm, the D50 particle size D2 of the zinc nanoparticles is 50nm, and the D50 particle size D3 of the nickel nanoparticles is 100nm. The rest is the same as in Embodiment 1, and will not be repeated here.

[0080] Example 3 This embodiment provides a negative electrode sheet. Compared with Embodiment 1, the only difference is that the D50 particle size D1 of the carbon black is 300nm, the D50 particle size D2 of the zinc nanoparticles is 20nm, and the D50 particle size D3 of the nickel nanoparticles is 100nm. The other aspects are the same as in Embodiment 1, and will not be repeated here.

[0081] Example 4 This embodiment provides a negative electrode sheet. Compared with Embodiment 1, the only difference is that the D50 particle size D1 of the carbon black is 30nm, the D50 particle size D2 of the zinc nanoparticles is 50nm, and the D50 particle size D3 of the nickel nanoparticles is 30nm. The rest is the same as in Embodiment 1, and will not be repeated here.

[0082] Example 5 This embodiment provides a negative electrode sheet. Compared with Embodiment 1, the only difference is that the D50 particle size D1 of the carbon black is 50nm, the D50 particle size D2 of the zinc nanoparticles is 30nm, and the D50 particle size D3 of the nickel nanoparticles is 50nm. The rest is the same as in Embodiment 1, and will not be repeated here.

[0083] Example 6 This embodiment provides a negative electrode sheet. The only difference from embodiment 5 is that the D50 particle size D1 of the carbon black is 20nm. The rest is the same as in embodiment 5 and will not be described again here.

[0084] Example 7 This embodiment provides a negative electrode sheet. Compared with embodiment 5, the only difference is that the D50 particle size D1 of the carbon black is 30nm. The rest is the same as that of embodiment 5, and will not be repeated here.

[0085] Example 8 This embodiment provides a negative electrode sheet. The only difference from embodiment 5 is that the D50 particle size D1 of the carbon black is 150nm. The rest is the same as in embodiment 5 and will not be described again here.

[0086] Example 9 This embodiment provides a negative electrode sheet. The only difference from embodiment 5 is that the D50 particle size D1 of the carbon black is 300nm. The rest is the same as in embodiment 5 and will not be described again here.

[0087] Example 10 This embodiment provides a negative electrode sheet. The only difference from embodiment 5 is that the D50 particle size D1 of the carbon black is 350nm. The rest is the same as in embodiment 5 and will not be described again here.

[0088] Example 11 This embodiment provides a negative electrode sheet. The only difference from embodiment 5 is that the D50 particle size D2 of the zinc nanoparticles is 10 nm. The rest is the same as in embodiment 5 and will not be described again here.

[0089] Example 12 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D2 of the zinc nanoparticles is 20nm. The rest is the same as Embodiment 5 and will not be described again here.

[0090] Example 13 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D2 of the zinc nanoparticles is 50nm. The rest is the same as Embodiment 5 and will not be described again here.

[0091] Example 14 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D2 of the zinc nanoparticles is 100nm. The rest is the same as Embodiment 5 and will not be described again here.

[0092] Example 15 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D3 of the nickel nanoparticles is 20nm. The rest is the same as Embodiment 5 and will not be described again here.

[0093] Example 16 This embodiment provides a negative electrode sheet. The only difference from Embodiment 5 is that the D50 particle size D3 of the nickel nanoparticles is 30nm. The rest is the same as in Embodiment 5 and will not be described again here.

[0094] Example 17 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D3 of the nickel nanoparticles is 100nm. The rest is the same as Embodiment 5 and will not be described again here.

[0095] Example 18 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the D50 particle size D3 of the nickel nanoparticles is 150nm. The rest is the same as Embodiment 5 and will not be described again here.

[0096] Example 19 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the D50 particle size D1 of the carbon black is 350nm, the D50 particle size D2 of the zinc nanoparticles is 70nm, and the D50 particle size D3 of the nickel nanoparticles is 117nm. The other aspects are the same as in Embodiment 5 and will not be repeated here.

[0097] Example 20 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the D50 particle size D1 of the carbon black is 30nm, the D50 particle size D2 of the zinc nanoparticles is 45nm, and the D50 particle size D3 of the nickel nanoparticles is 75nm. The other aspects are the same as in Embodiment 5, and will not be repeated here.

[0098] Example 21 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the D50 particle size D1 of the carbon black is 300nm, the D50 particle size D2 of the zinc nanoparticles is 26nm, and the D50 particle size D3 of the nickel nanoparticles is 43nm. The other aspects are the same as in Embodiment 5, and will not be repeated here.

[0099] Example 22 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the mass of carbon black accounts for 60% of the mass of the composite carbon layer, the mass of nano zinc particles accounts for 17.5% of the mass of the composite carbon layer, and the mass of nano nickel particles accounts for 17.5% of the mass of the composite carbon layer. The rest is the same as in Embodiment 5, and will not be repeated here.

[0100] Example 23 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the mass of carbon black accounts for 65% of the mass of the composite carbon layer, the mass of nano zinc particles accounts for 15% of the mass of the composite carbon layer, and the mass of nano nickel particles accounts for 15% of the mass of the composite carbon layer. The rest is the same as in Embodiment 5, and will not be repeated here.

[0101] Example 24 This embodiment provides a negative electrode sheet. Compared with Embodiment 5, the only difference is that the mass of carbon black accounts for 85% of the mass of the composite carbon layer, the mass of nano zinc particles accounts for 5% of the mass of the composite carbon layer, and the mass of nano nickel particles accounts for 5% of the mass of the composite carbon layer. The rest is the same as in Embodiment 5, and will not be repeated here.

[0102] Example 25 This embodiment provides a negative electrode sheet, which differs from Embodiment 5 only in that the stainless steel foil is replaced with nickel foil. All other aspects are the same as in Embodiment 5 and will not be described again here.

[0103] Comparative Example 1 This comparative example provides a negative electrode sheet. Compared with Example 5, the only difference is that the composite carbon layer does not include nano-zinc particles and nano-nickel particles, and the mass of carbon black accounts for 95% of the mass of the composite carbon layer. The rest is consistent with Example 1 and will not be repeated here.

[0104] Comparative Example 2 This comparative example provides a negative electrode sheet. Compared with Example 5, the only difference is that the composite carbon layer does not include nano-zinc particles, the mass of carbon black accounts for 83.8% of the mass of the composite carbon layer, and the mass of nano-nickel particles accounts for 11.2% of the mass of the composite carbon layer. The rest is the same as Example 5, and will not be repeated here.

[0105] Comparative Example 3 This comparative example provides a negative electrode sheet. Compared with Example 5, the only difference is that the composite carbon layer does not include nano-nickel particles, the mass of carbon black accounts for 83.8% of the mass of the composite carbon layer, and the mass of nano-zinc particles accounts for 11.2% of the mass of the composite carbon layer. The rest is the same as Example 5, and will not be repeated here.

[0106] Comparative Example 4 This comparative example provides a negative electrode sheet, which differs from Example 1 only in that the D50 particle size D1 of the carbon black is 150nm, the D50 particle size D2 of the zinc nanoparticles is 300nm, and the D50 particle size D3 of the nickel nanoparticles is 1550nm. The other aspects are the same as in Example 1, and will not be repeated here.

[0107] Comparative Example 5 This comparative example provides a negative electrode sheet, which differs from Example 1 only in that the D50 particle size D1 of the carbon black is 640 nm, the D50 particle size D2 of the zinc nanoparticles is 40 nm, and the D50 particle size D3 of the nickel nanoparticles is 20 nm. The other aspects are the same as in Example 1, and will not be repeated here.

[0108] The negative electrode sheets of Examples 1-25 and Comparative Examples 1-5 were assembled into solid-state batteries, and the performance of the solid-state batteries was tested. The results are shown in Table 1.

[0109] The solid-state battery assembly process is as follows: (1) LPSC is added to the model battery and held at 400MPa for 6 minutes to obtain a solid electrolyte membrane; (2) NCM, LPSC and vapor-grown carbon fiber powder (VGCF) are mixed at a mass percentage of 70%:28%:2% to obtain a positive electrode composite powder, with an areal loading of 200g / m 2 Add the positive electrode composite powder to one side of the model battery, hold the pressure at 400MPa for 6 minutes, and form a positive electrode sheet on the solid electrolyte membrane; (3) Cut the negative electrode sheets of Examples 1 to 25 and Comparative Examples 1 to 5 into small round pieces with a diameter of 10mm, add the small round pieces to the other side of the model battery, hold the pressure at 400MPa for 6 minutes, and form a negative electrode sheet on the side of the solid electrolyte membrane away from the positive electrode sheet.

[0110] The solid-state battery performance was tested as follows: an external pressure of 3 MPa was applied using an aluminum clamp and a gasket, and the battery was charged at a constant current rate of 0.2C to 4.3V. Subsequently, it was charged at a constant voltage of 4.3V until the current was less than 0.05C. The above constant current + constant voltage process constituted the entire charging process of the battery. After resting for 30 minutes, the battery was discharged at a constant current rate of 0.2C to 2.5V. The capacity obtained during the discharge was the capacity of the battery at a 0.2C rate. The above charging process + discharging process constituted a complete cycle of the battery.

[0111] Battery capacity was tested using an electrochemical workstation.

[0112] Cycle count refers to the number of cycles a battery completes before it retains 80% of its capacity.

[0113] Table 1

[0114] As can be seen from the data in Examples 1-4 and Comparative Examples 4-5 in Table 1, the battery performance is better when the ratio of the D50 particle size of carbon black, zinc nanoparticles and nickel nanoparticles satisfies 0.6≤D1 / D2≤15, 0.3≤D1 / D3≤10, and 0.6≤D3 / D2≤5. This is mainly because when the ratio of the D50 particle size of carbon black, zinc nanoparticles and nickel nanoparticles satisfies a specific relationship, the three materials are stacked in a specific way to form a uniformly distributed lithiophilic site and conductive network in the composite carbon layer, while ensuring good skeletal stability of the composite carbon layer, so that the battery exhibits excellent electrochemical performance. However, when the above particle size ratio range cannot be satisfied at the same time, the battery performance is poor.

[0115] Data from Examples 5-21 show that the battery performance is superior when simultaneously satisfying (1) 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, 1≤D3 / D2≤3.3 and (2) the D50 particle size of carbon black is 30nm~300nm, the D50 particle size of zinc nanoparticles is 20nm~50nm, and the D50 particle size of nickel nanoparticles is 30nm~100nm. Specifically: Data from Examples 5-10 show that as the D50 particle size of carbon black gradually increases, the battery capacity and cycle life exhibit a trend of first increasing and then decreasing. Example 5 shows that the battery performance is optimal when the D50 particle size of the carbon black and the nano-nickel particles are the same, and the nano-zinc particles are relatively small. This may be because when the D50 particle size of carbon black and the nano-nickel particles are the same, the nano-nickel particles can be more evenly distributed among the carbon black particles, providing good support for the carbon skeleton. Simultaneously, the high specific surface area of ​​the nano-zinc particles can be evenly distributed within the pores formed by the carbon black, improving the structure and performance of the negative electrode, thereby enhancing battery performance. In Examples 6 and 8-9, although there are some deviations in the D50 particle size of the carbon black and the nano-nickel particles, the relatively smaller particles can appropriately agglomerate into secondary particles, resulting in a higher strength and more uniform pores in the carbon skeleton formed by the synergistic interaction of carbon black and nano-nickel particles, thus leading to better performance of the negative electrode and the battery. When the carbon black particle size is too small, severe agglomeration occurs between different carbon black particles, making them difficult to disperse and affecting the structure and performance of the negative electrode. When the carbon black particle size is too large, the utilization rate of a single particle is low, and the local potential inside the electrode is too high, resulting in severe electrode polarization and affecting battery performance. Figure 1 It can be seen that the charging capacity of Example 5 is 190mAh / g, the capacity retention rate of the first charge and discharge cycle is relatively high, and the charge and discharge curve is relatively smooth, indicating that the battery cycle process is relatively stable.

[0116] Data from Examples 5 and 11-14 show that when the D50 particle size of the zinc nanoparticles is between 20nm and 50nm, the silver nanoparticles can be more uniformly distributed in the pores of the composite carbon layer. At the same time, the zinc nanoparticles have more active sites, which makes the deposition of lithium ions more complete, rapid and uniform, thus resulting in excellent performance of the negative electrode and the battery.

[0117] Data from Examples 5 and 15-18 show that when the D50 particle size of the nickel nanoparticles deviates significantly from that of the carbon black, the battery performance is poor. This may be because when the D50 particle size of the nickel nanoparticles is too small, they can only simply fill the gaps between the carbon black particles and cannot effectively stack with the carbon black, thus failing to provide support for the carbon skeleton. This results in poor structural stability of the composite carbon layer, leading to poor battery performance. Conversely, when the D50 particle size of the nickel nanoparticles is too large, it may, to some extent, damage the structure of the carbon skeleton, which is detrimental to improving battery performance.

[0118] As can be seen from the data in Examples 19-21, when only one of the following conditions is met: (1) 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, 1≤D3 / D2≤3.3 and (2) the D50 particle size of carbon black is 30nm~300nm, the D50 particle size of zinc nanoparticles is 20nm~50nm, and the D50 particle size of nickel nanoparticles is 30nm~100nm, the synergistic effect of carbon black, zinc nanoparticles and nickel nanoparticles is limited, thereby weakening the performance of the battery.

[0119] As can be seen from the data of Examples 5 and Examples 22-24, as the proportion of carbon black in the composite carbon layer increases and the proportion of nano-zinc particles and nano-nickel particles decreases, the battery capacity and cycle number show a trend of first increasing and then decreasing. When the mass proportion of carbon black in the composite carbon layer is 65%~85% and the mass proportion of nano-zinc particles and nano-nickel particles is 5%~15% each, the overall performance of the battery is better. This may be because when the proportion of carbon black is too small, a relatively continuous carbon skeleton and three-dimensional conductive network cannot be formed, and the cost will also increase. When the proportion of nano-zinc particles and nano-nickel particles is too small, they cannot play their role, resulting in poor performance of the rechargeable battery.

[0120] As can be seen from the data in Example 25, when nickel foil is used as the current collector, the battery assembled from the negative electrode sheet exhibits excellent performance.

[0121] The data from Comparative Examples 1 to 3 show that when one or both of the nano-zinc particles and nano-nickel particles are not added to the composite carbon layer, the battery performance drops significantly, further demonstrating that carbon black, nano-zinc particles, and nano-nickel particles can significantly improve battery performance through synergy.

[0122] In summary, based on the data from the embodiments and comparative examples of this application, it can be seen that when the particle size ratios of the micro / nano carbon-based framework material, the lithiophilic micro / nano and micro / nano metal-based framework material in the composite carbon layer satisfy 0.6≤D1 / D2≤15, 0.3≤D1 / D3≤10, and 0.6≤D3 / D2≤5, the three materials can be stacked in a specific manner to form uniformly distributed lithiophilic sites and conductive networks in the composite carbon layer, achieving uniform deposition of lithium ions while ensuring good framework stability of the composite carbon layer, resulting in better battery performance.

[0123] The foregoing has provided a detailed description of a negative electrode sheet and its preparation method, as well as a solid-state battery, provided in the embodiments of this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A negative electrode sheet, characterized in that, include: Negative electrode current collector; and A composite carbon layer is disposed on at least one side of the negative electrode current collector. The composite carbon layer includes a micro / nano carbon-based framework material, a lithiophilic micro / nano metal material, and a micro / nano metal-based framework material. The D50 particle size of the micro / nano carbon-based framework material is D1, the D50 particle size of the lithiophilic micro / nano metal material is D2, and the D50 particle size of the micro / nano metal-based framework material is D3. Among them, 0.6≤D1 / D2≤15, 0.3≤D1 / D3≤10, and 0.6≤D3 / D2≤5.

2. The negative electrode sheet according to claim 1, characterized in that, 1≤D1 / D2≤10, 0.5≤D1 / D3≤6, 1≤D3 / D2≤3.

3.

3. The negative electrode sheet according to claim 1 or 2, characterized in that, 30nm≤D1≤300nm; and / or, 20nm≤D2≤50nm; and / or, 30nm≤D3≤100nm.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The mass of the micro / nano carbon-based framework material accounts for 60% to 95% of the mass of the composite carbon layer, the mass of the lithiophilic micro / nano metal material accounts for 1% to 20% of the mass of the composite carbon layer, and the mass of the micro / nano metal-based framework material accounts for 1% to 20% of the mass of the composite carbon layer.

5. The negative electrode sheet according to claim 4, characterized in that, In the composite carbon layer, the mass of the micro / nano carbon-based framework material accounts for 65% to 85% of the mass of the composite carbon layer, the mass of the lithiophilic micro / nano metal material accounts for 5% to 15% of the mass of the composite carbon layer, and the mass of the micro / nano metal-based framework material accounts for 5% to 15% of the mass of the composite carbon layer.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that, The micro / nano carbon-based framework material includes at least one of carbon black and hard carbon; and / or, The lithiophilic micro / nano metallic material includes at least one of zinc nanoparticles, tin nanoparticles, bismuth nanoparticles, magnesium nanoparticles, and aluminum nanoparticles; and / or, The micro / nano metal matrix framework material includes at least one of nano-nickel particles, nano-copper particles, and nano-indium particles; and / or, The negative electrode current collector contains at least one of stainless steel foil, nickel foil, and copper foil.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that, The thickness of the composite carbon layer is 1 μm to 10 μm.

8. The negative electrode sheet according to claim 5, characterized in that, The composite carbon layer also includes a binder, the mass of which accounts for 2% to 10% of the mass of the composite carbon layer.

9. A method for preparing a negative electrode sheet according to any one of claims 1 to 8, characterized in that, include: Provide negative electrode current collector; A carbon coating slurry is obtained by mixing micro / nano carbon-based framework materials, lithiophilic micro / nano metal materials, micro / nano metal-based framework materials, binders, and solvents, wherein the solid content of the carbon coating slurry is 20wt%~30wt%. The carbon coating slurry is coated on at least one side of the negative electrode current collector, and after drying, a composite carbon layer is formed on the surface of the negative electrode current collector.

10. A solid-state battery, characterized in that, This includes the negative electrode sheet as described in any one of claims 1 to 8, or the negative electrode sheet prepared by the method for preparing the negative electrode sheet as described in claim 9.